Development of blended learning media on similarity and congruence topics - Ismet, Ismet; Yerizon, Yerizon; Fauzan, Ahmad; Asmar, Ali (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: The integration of technology in education has become increasingly important in enhancing student engagement. Mathematics, as a foundational subject, often requires innovative approaches to improve students' problem-solving skills and conceptual understanding. Blended learning combines traditional and digital methods, offering a flexible and effective solution for teaching complex mathematical topics.Aim: This research aims to develop valid, practical, and effective learning media for teaching the topics of similarity and congruence, enabling students to better understand these mathematical concepts. The media is designed based on the Blended Learning approach.Method: The development process follows the Plomp model, which consists of three stages: (1) the initial investigation stage to identify needs and context, (2) the product development stage where the media is designed and refined, and (3) the assessment stage to evaluate its validity, practicality, and effectiveness.Results: The developed learning media was validated with a validity score of 86.99, categorized as very valid. It also achieved a practicality score of 87.01, indicating it is very practical, and an effectiveness score of 83.33, categorized as effective.Conclusion: Blended Learning-based media for teaching similarity and congruence is a valid, practical, and effective tool that can enhance students' understanding of the topics.